Comparing Transformation Disclosure Trends of Publicly Funded Universities in South Africa - Sameera Abed; Barry Ackers (Indonesian Journal of Sustainability Accounting and Management, 2022)
More than 25 years into democracy, South Africa’s higher educational landscape remains challenged by the slow pace of transformation and the residual inequality of apartheid. We utilize a mixed-methods research approach to analyze, interpret, and compare transformation-related disclosures among publicly funded universities, with reference to their historical apartheid-era categorization. We particularly explore the mechanisms introduced to improve academic access and success of students from previously disadvantaged groups. Moreover, we identify the challenges that have contributed to the slow pace of transformation. ATLAS.ti was used to analyze and interpret the transformation-related disclosures in publicly available annual reports of the universities included in this study. We find that historically advantaged universities tend to disclose more support mechanisms, but historically disadvantaged ones face greater infrastructural challenges. We offer a unique perspective on the transformation support mechanisms and challenges experienced by public universities in South Africa based on their historical classification.